Randomized Open Label Clinical Trial on the Efficacy of Saptamrita Ghrita Tarpana, Eye Exercises and Shatavaryadi Churna in Vataja Timira w.s.r. to Astigmatism (AYUSHDHARA, 2023)
Astigmatism is a type of refractive error in which refraction varies in different meridians of the eyes; consequently, the light rays entering the eye cannot converge to a point of focus but form various focal lines. All the refractive disorders including astigmatism come under Timira. In modern science the treatment options of astigmatism include spectacles, contact lens, and Lasik surgery which are very expensive. Hence in order to provide efficient and better cure by cost effective method through Ayurveda, this study was planned which incorporates Kriya Kalpa procedure, oral drug, and eye exercises to tackle it efficiently. Aim: To evaluate the efficacy of Saptamrita Ghrita Tarpana and Eye exercises in management of Vataja Timira w.s.r. to astigmatism. Objectives: 1. To evaluate the effect of eye exercises and Shatavaryadi Churna in Vataja Timira w.s.r. to astigmatism. 2. To evaluate the effect of Saptamritam Ghrita Tarpana and Shatavaryadi Churna in Vataja Timira w.s.r. to astigmatism. Materials and Methods: 30 patients with Vataja Timira were randomly assigned to two groups for a clinical trial. Result: The clinical data shows that the effect of therapy on Vataja Timira is 60% in Group A and 51.04% in Group B. Conclusion: It can be concluded that clinically Saptamrita ghrita Tarpana, Shatavaryadi churna and eye exercises combine work better to manage the Vataja Timira.